NDRG1 facilitates the replication and persistence of Kaposi’s sarcoma-associated herpesvirus by interacting with the DNA polymerase clamp PCNA - Zhang, Fang (PLoS Pathog, 2019)
Kaposi’s sarcoma-associated herpesvirus (KSHV) latently infects host cells and establishes lifelong persistence as an extra-chromosomal episome in the nucleus. To persist in proliferating cells, the viral genome typically replicates once per cell cycle and is distributed into daughter cells. This process involves host machinery utilized by KSHV, however the underlying mechanisms are not fully elucidated. In present study, we found that N-Myc downstream regulated gene 1 (NDRG1), a cellular gene known to be non-detectable in primary B cells and endothelial cells which are the major cell types for KSHV infection in vivo, was highly upregulated by KSHV in these cells. We further demonstrated that the high expression of NDRG1 was regulated by latency-associated nuclear antigen (LANA), the major viral latent protein which tethers the viral genome to host chromosome and plays an essential role in viral genome maintenance. Surprisingly, knockdown of NDRG1 in KSHV latently infected cells resulted in a significant decrease of viral genome copy number in these cells. Interestingly, NDRG1 can directly interact with proliferating cell nuclear antigen (PCNA), a cellular protein which functions as a DNA polymerase clamp during DNA replication. Intriguingly, we found that NDRG1 forms a complex with LANA and PCNA and serves as a scaffold protein bridging these two proteins. We further demonstrated that NDRG1 is critical for mediating LANA to recruit PCNA onto terminal repeat (TR) of KSHV genome, and facilitates viral DNA replication and episome persistence. Taken together, our findings suggest that NDRG1 plays an important role in KSHV viral genome replication, and provide new clues for understanding of KSHV persistence.